Strategy for Cultural Transformation in Islamic Boarding Schools: An Integration Model of Islamic Values, Local Wisdom, and Modern Management for Improving Teacher Performance - Yamin Kamaludin; Azhar Affandi; Horas Djulius (PT. Publikasiku Academic Solution, 2025)
Pesantren (Islamic boarding schools), as crucial educational institutions, face significant challenges in the modern era, where teacher performance is often hampered by a work culture that is not yet optimal. This research aims to formulate and analyze effective strategies for transforming the work culture of pesantren. Using a qualitative exploratory case study method, this research was conducted at Pondok Pesantren Baiturrahman and several other pesantren in Bandung Regency, with data collected through in-depth interviews, Focus Group Discussions (FGDs), observations, and documentation studies. The research results indicate that the suboptimal work culture and teacher performance stem from systemic weaknesses in six areas: management, human resources (HR), processes, policies, technology utilization, and the culture itself. As a solution, this research proposes a transformation strategy centered on the concepts of “BAROKAH Management” (blessing management), “DIGEMARI Personality” (liked personality), and the application of local wisdom “7U & 4K.” The main contribution of this research is the formulation of the “3 in One Work Culture” model, a new framework that integrates noble Islamic values, modern professional management standards, and Sundanese local wisdom. This model offers a holistic and contextual strategic guide for pesantren to build a superior work culture to achieve sustainable improvement in teacher performance.